The Influence of Financial System in Albanian Economy - Guga, Klaudja; Mehilli, Terida; Naqellari, Alqi; Demo, Ervin (Richtmann Publishing, 2012)
During the last years Albanian Financial System has continued its stable growth. The quite good financial outcome, in bothbanking sector and non-bank financial sector, was due to the better use of the financial sources and the ongoing relatively quickexpansion of the investment activities with high return. The long-term trend for a gradual decline of the capital adequacy indicator of thefinancial system and particularly of the banking sector has continued, but the declining rate is reducing. The assets of the financialsystem have been steadily growing, but the weight of the non-banking financial sector still remains low, thus limiting the contribution ofthis sector on the stable development of the overall financial system. This article discusses the progress and the influence that thefinancial system has itself as a creator of money, not only lending. Is good for our analysis to remember how this concept has a directimpact on economic factors such as: the commercial debt that has been raised in recent months, inflation which has increased, anddirect investments which have fallen. Naturally we are going to illustrate the principal methods that the financial management uses toprevent the various risks that represent the financial market, and which are the most appropriate indicators to analyze the situation of theAlbanian financial system.